Molecular identification of Fusarium species associated with bakanae disease of rice (Oryza sativa) in India - BASHYAL, B M; AGGARWAL, RASHMI (The Indian Journal of Agricultural Sciences, 2013)
Fifty isolates of Fusarium spp (Gibberella fujikuroi species complex) were obtained from rice seeds collected from major rice-growing regions of India. Gibberella fujikuroi species complex were detected in popularly grown rice varieties with infection ranging from 1% to 24%. Pathogenicity test of Fusarium spp was performed in susceptible rice variety Pusa 1121, which showed reduced seed germination and possessed varying ability to cause symptoms of bakanae on rice. Maximum incidence of slender and chlorotic leaves were produced by F. fujikuroi (90%), while maximum incidence of crown rot and stem rot was produced by F. moniliforme (50%). Use of ITS sequence gave reliable identification of pathogenic isolates of Fusarium spp associated with bakanae disease of rice. Three Fusarium spp, viz Fusarium moniliforme, Fusarium fujikuroi and Fusarium proliferatum were found associated with bakanae disease of rice in India. Phylogenetic studies showed a broad genetic variation among different species isolates that were distributed into three different clades. This finding provides new information on the bakanae disease and its distribution in India which could be helpful for the development of management strategies.